1985
DOI: 10.1901/jaba.1985.18-323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Training Manual for the Acquisition of Behavioral Assessment Interviewing Skills

Abstract: Two procedures were used to teach behavioral assessment interviewing skills: a training manual and one-to-one instruction that included modeling, rehearsal, and feedback. Two graduate students and two advanced undergraduates were trained with each procedure. Interviewing skills were recorded in simulated assessment interviews conducted by each student across baseline and treatment conditions. Each training procedure was evaluated in a multiple baseline across students design. The results showed that both proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Previous research has shown that when a manual is specifically designed to teach a skill, it may be an effective method for establishing the repertoire. For example, Miltenberger and Fuqua (1985) evaluated the effectiveness of both an instructional manual and behavioral skills training on the acquisition of behavioral interviewing skills and found that both instructional methods were equally successful in teaching the target skills. According to these results, it is possible that the written instructions provided in the VB-MAPP guide and protocol (Sundberg 2008) are sufficient to teach professionals to administer the assessment.…”
Section: Verbal Behavior Milestones Assessment and Placement Programmentioning
confidence: 99%
“…Previous research has shown that when a manual is specifically designed to teach a skill, it may be an effective method for establishing the repertoire. For example, Miltenberger and Fuqua (1985) evaluated the effectiveness of both an instructional manual and behavioral skills training on the acquisition of behavioral interviewing skills and found that both instructional methods were equally successful in teaching the target skills. According to these results, it is possible that the written instructions provided in the VB-MAPP guide and protocol (Sundberg 2008) are sufficient to teach professionals to administer the assessment.…”
Section: Verbal Behavior Milestones Assessment and Placement Programmentioning
confidence: 99%
“…It is designed to obtain the informant's (teacher, staff, or parent) report of a partic ular behavior and its related variables (Bergan, 1977;Cone, 1987;O'Leary & Wilson, 1986). A complete interview should contain questions about the topogra phy of the behavior problem, antecedent events, con sequent events, and other information to determine the variables maintaining behavior and to select appropri ate treatment procedures (Iwata, Wong, Reardon, Dorsey, & Lau, 1982b;Miltenberger & Fuqua, 1985;Miltenberger & Veltum, 1988).…”
Section: Informant Assessmentmentioning
confidence: 99%
“…These findings are not unique; several studies have demonstrated that written materials are less effective than modeling, role playing, and feedback in creating behavior change (Nay, 1975;Quilitch, 1975). There is some evidence, however, suggesting that written protocols can effect significant behavior change (Friman, Finney, Glasscock, Weigel, & Christopherson, 1986;Miltenberger & Fuqua, 1986). Because the use of a training manual offers a potentially costeffective approach to infant-care training, an experimental analysis of the effects of the manual as revised for Experiment 2 or variants thereof with fathers and their newborns during the early postpartum period merits further investigation.…”
Section: Discussionmentioning
confidence: 99%